Early tumor shrinkage in patients with metastatic colorectal cancer receiving first-line treatment with cetuximab combined with either CAPIRI or CAPOX: An analysis of the German AIO KRK 0104 trial. (June 2013) - Modest, Dominik P.; Laubender, Ruediger P.; Stintzing, Sebastian; Giessen, Clemens; Schulz, Christoph; Haas, Michael; Mansmann, Ulrich; Heinemann, Volker
Abstract: Purpose. This study investigated the impact of early tumor shrinkage (ETS) on progression-free- (PFS) and overall survival (OS) in patients with metastatic colorectal cancer (mCRC) treated within the AIO KRK 0104 trial as first-line therapy. Moreover, correlations of ETS with clinical characteristics and prognostic markers were evaluated. Patients and methods. In total, 121 patients were included into this analysis. Patients were treated with cetuximab combined with either CAPIRI or CAPOX. ETS at six weeks was defined as a relative change of ≥ 20% in the sum of the longest diameters of target lesions compared to baseline. Survival times were compared between patients with ETS ≥ 20% versus no-ETS. Results. ETS ≥ 20% was observed in 59% of all patients with KRAS wild-type tumors. In these patients ETS ≥ 20% was associated with higher overall response rate (82% vs. 19%, p < 0.001). Also, PFS (8.9 vs. 4.7 months, p < 0.001) and OS (31.6 vs. 15.8 months, p = 0.005) were significantly superior in ETS ≥ 20% of patients compared to no-ETS. In patients with KRAS mutant mCRC ETS ≥ 20% neither had an effect on PFS nor OS. Cetuximab-induced skin toxicity correlated with the occurrence of ETS ≥ 20% (p = 0.002). Conclusion. In patients with KRAS wild-type tumors treated with cetuximab plus capecitabine-based chemotherapy ETS ≥ 20% is an important predictor of favorable outcome.